A Stakeholder Approach to the Assessment of (and for) Sustainable Service-Learning Projects - Cărămidaru Ibrian (Discourse and Communication for Sustainable Education)
The aim of this article is to provide a model for assessing service-learning projects mediated by a stakeholder approach to managing such educational pursuits. The method used for substantiating this proposal consists of matching the process of stakeholder analysis, customised for experiential learning, with the project scope and monitoring techniques for service-learning projects, in the context of institutional coordination. Upon such informational structure, an inventory of metrics suitable for the array of actors forming the constituency of service-learning settings is built up. Sustainability is aimed through institutional settings for sustainable projects, ongoing consultation with multiple stakeholder categories, and reporting on various outcomes. A discussion is provided on the difficulties of inter-project comparisons, assessing qualitative long-term outcomes and on whether this manifold cast of service-learning projects might aptly aim at estimates for the aggregated social value assessments of this type of project.